Ferrocene nanoparticles and preparation method and application thereof
By preparing spherical ferrocene nanoparticles rich in Fe2+, the problem of iron ions depletion in the catalysis process of iron-based nanomaterials was solved, long-term cyclic catalysis was achieved, and good results were shown in the antibacterial field.
Patent Information
- Application Number
- CN202310171675.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-28
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2043-02-28
AI Technical Summary
The iron ions are gradually depleted during the catalysis process of existing iron-based nanomaterials, making it difficult to achieve long-term cyclic catalysis, and the antibacterial effect is not ideal.
By dissolving the ferrocene derivative in a solvent, reacting and centrifuging, washing and drying, uniform spherical ferrocene nanoparticles were prepared, and the cyclic catalysis was promoted using their abundant Fe2+, and the material was found to have good photocatalysis. Bactericidal properties.
Long-term cycle catalysis of ferrocene nanoparticles has been achieved, catalytic efficiency has been improved, and it has shown wide application potential in the field of antibacterial.
Smart Images

Figure CN116143847B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of new nano materials, and specifically relates to ferrocene nanoparticles and a preparation method and application thereof. Background Art
[0002] Nanomaterials are materials with new uses that are obtained by coupling or synergistically recombining several substances with different physical and chemical properties. Nanomaterials have a special structure. Their tiny size and high proportion of surface atoms lead to their quantum size effect and other special physical and chemical properties. In addition to the properties of the raw materials themselves, the newly synthesized nanomaterials can also show other new properties, breaking through the limitations of the functions of a single material. Nanoparticles usually also have a large specific surface area, with a specific surface area of hundreds or even thousands of square meters per gram of solid material, which makes them highly active adsorbents and catalysts, and have a wide range of uses in biomedicine, environmental protection, antibacterial and anti-tumor.
[0003] Zhang Yu, Gu Ning et al. published a paper on Depletable peroxidase-like activity of Fe3O4 nanozymes accompanied with separate migration of electrons and iron ions in Nature Communications. They believed that ordinary iron-based nanomaterials would continuously consume Fe3O4 as the catalytic time increases. For example, in the catalytic process of H2O2, H2O2 would continuously consume Fe 2+ , converting it into Fe 3+ , and this process is usually irreversible and difficult to obtain from Fe 3+ Back to Fe 2+ Therefore, the entire catalytic process is a process in which the iron-based nanomaterials are gradually depleted. 2+ The content will gradually decrease and quickly become ineffective, making it difficult to make Fe 2+ and Fe 3+ The cycle achieves the purpose of long-term catalysis.
[0004] Ferrocene does not react with acid, alkali, or ultraviolet light, and its chemical properties are stable and not easy to decompose. In addition, since the central iron atom of ferrocene and the two upper and lower cyclopentadienyl rings fit closely together, there are almost no free iron ions and cyclopentadienyl rings in the molecule, making ferrocene rich in Fe. 2+Therefore, applying the nanocomposite materials of ferrocene and its derivatives to the field of nanocatalysis will greatly improve the catalytic efficiency and can be used in different catalytic systems. At present, there are still some problems in the use of nanocatalysts: first, it is difficult for ferrocene and its derivatives to form nanoparticles with regular shapes; second, the iron-based nanomaterials will gradually be exhausted after long-term catalysis, making it difficult to circulate catalysis for a long time; third, the antibacterial effect of nanomaterials is still not ideal. Summary of the invention
[0005] In order to solve the existing problems in ferrocene catalysis, the present invention provides a ferrocene nanoparticle with recyclable catalysis. The ferrocene derivative is dissolved in a solvent and reacted to obtain the nanoparticle. The process is simple. The nanoparticle is uniformly spherical and has a particle size of 1 to 5 μm. There is a large amount of Fe in the nanomaterial. 2+ , which promoted the cyclic catalysis of ferrocene and greatly improved the catalytic efficiency; at the same time, it was found that the material has antibacterial applications.
[0006] The technical solution of the present invention is as follows:
[0007] A ferrocene nanoparticle is obtained by dissolving a ferrocene derivative in a solvent, reacting, centrifuging, washing and drying;
[0008] The ferrocene derivative is 1,1-ferrocene dicarboxylic acid; and the solvent is N, N-dimethylformamide.
[0009] Preferably, the reaction is carried out in an autoclave at 120-200°C for 5-10 h.
[0010] Preferably, the nanoparticles are uniformly spherical and have a particle size of 1 to 5 μm.
[0011] Preferably, the washing is water washing.
[0012] The method for preparing the ferrocene nanoparticles comprises the following steps:
[0013] (1) dissolving a ferrocene derivative in a solvent;
[0014] (2) pouring the solution of step (1) into an autoclave and keeping it at 120-200°C for 5-10 hours;
[0015] (3) Centrifuge, wash and dry.
[0016] The above-mentioned ferrocene nanoparticles are used as catalysts for catalyzing H2O2.
[0017] The above-mentioned ferrocene nanoparticles are used as catalysts in photocatalytic sterilization.
[0018] Beneficial Effects of the Invention
[0019] The ferrocene nanoparticles (Fc NPs) provided by the present invention require very few raw materials for synthesis, only one raw material and one solvent are needed, and the solvent DMF only plays a dissolving role, and the nanoparticles can be synthesized only through the self-coordination of a single raw material itself; the synthesized Fc NPs have a large specific surface area, so that when used as a catalyst, they have sufficient active sites and good catalytic activity, thereby improving the catalytic efficiency; and the synthesized Fc NPs have the characteristics of good biocompatibility, simple synthesis, green and pollution-free, and easy separation, so that long-term catalysis and recycling can be achieved; in addition, Fc NPs have good photocatalytic bactericidal performance and are widely used in the antibacterial field. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is a schematic diagram of the preparation method of ferrocene nanomaterials (Fc NPs) in Example 1;
[0021] Figure 2 is a scanning electron microscopy image of Fc NPs prepared in Example 1;
[0022] Figure 3 is the infrared spectrum of Fc NPs prepared in Example 1;
[0023] Figure 4 is the nitrogen adsorption-desorption isotherm of Fc NPs prepared in Example 1;
[0024] Figure 5 The UV-visible absorption spectra of the Fc NPs prepared in Example 1 and the raw material Fc(COOH)2 required for synthesis;
[0025] Figure 6 is the XPS spectrum of Fc NPs prepared in Example 1;
[0026] Figure 7 is the Fe 2p XPS high-resolution spectrum of Fc NPs prepared in Example 1;
[0027] Figure 8 is the UV-visible absorption spectrum curve of Fc NPs prepared in Example 1 in the presence of ABTS and H2O2;
[0028] Fig. 9 The Fe content of the Fc NPs prepared in Example 1 after long-term catalysis for different periods of time 2+ with Fe 3+ Graph of proportions changing over time;
[0029] Fig.10 This is the survival rate curve of Escherichia coli after being treated with Fc NPs prepared in the embodiment of the invention;
[0030] Fig.11 The photos are of colony agar plates of Escherichia coli treated with Fc NPs prepared in the examples of the invention under different conditions. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0032] Example 1
[0033] A method for preparing ferrocene nanoparticles comprises the following steps:
[0034] (1) Disperse 328.9 mg of ferrocene dicarboxylic acid (Fc(COOH)2, 1.2 mmol) in 24 mL of N, N-dimethylformamide (DMF), stir and sonicate at room temperature for 30 min to fully dissolve it.
[0035] (2) Transfer the mixed solution to a reactor and react in an oven at 180 °C for 6 h.
[0036] (3) After the reaction is completed, cool to room temperature, remove the supernatant, and centrifuge the precipitate (8000 rpm, 10 min) to obtain Fc NPs. The obtained precipitate is washed three times with DMF and water respectively. The obtained Fc NPs precipitate is dried at 60 °C to a black powder and stored at 4 °C for future use.
[0037] Embodiment 2:
[0038] In order to explore the peroxidase-like catalytic activity of Fc NPs, the catalytic ability of Fc NPs to H2O2 was detected using 2,2-azino-di(3-ethyl-benzothiazole-6-sulfonic acid) diammonium salt (ABTS) as a substrate. The specific steps are as follows:
[0039] (1) Add 5 μL of Fc NPs (3.6 mM), 50 μL of ABTS (2 mM), and 50 μL of H2O2 solution (100 mM) into 1895 μL of 2-morpholineethanesulfonic acid buffer (MES Buffer, pH 4.2), respectively.
[0040] (2) The Fc NPs in (1) were replaced with an equal amount of Fc(COOH)2 and an equal volume of water, which served as the raw material control group and the blank control group, respectively.
[0041] (3) After incubating the above three groups of solutions at room temperature for 180 min, their absorbance was immediately detected using a UV spectrophotometer.
[0042] Embodiment 3:
[0043] In order to study the cyclic catalytic activity of Fc NPs, the ratio of iron in different valence states after co-incubation of Fc NPs with H2O2 was detected by XPS. 60 mg of Fc NPs were added to 40 mL of H2O2 aqueous solution (500 μM). They were divided into two groups, one group was stirred at room temperature for 5 min, and the other group was stirred in an ice water bath for 0.5 min. After the reaction, the product was centrifuged, dried, recovered and characterized by XPS to test the Fe content in the material after short-term catalysis. 2+ with Fe 3+ The proportion of.
[0044] In addition, in order to study the long-term cyclic catalytic effect of Fc NPs, 40 mg of Fc NPs were added to 40 mL of H2O2 aqueous solution (10 μM), and the mixture was placed at room temperature for 0d (untreated), 2d, 4d, and 6d. After the reaction, the product was centrifuged, dried, recovered, and characterized by XPS to test the Fe content in the material after long-term catalysis. 2+ with Fe 3+ proportion.
[0045] Embodiment 4:
[0046] Gram-negative (-) bacteria Escherichia coli DH5α (E. Coli) were cultured in LB medium in an incubator at 37°C and used as an antibacterial model. In the antibacterial assay, the bacterial solution of E. coli (OD 600 = 0.4) and incubated with the material or further irradiated with a xenon lamp to detect the antibacterial effect of the material.
[0047] (1) The E. coli culture was divided into 6 groups and treated as follows: (1) E.Coli + PBS; (2) E.Coli + PBS + Xe lamp; (3) E.Coli + Fc(COOH)2; (4) E.Coli + Fc(COOH)2 + Xe lamp; (5) E.Coli + Fc NPs and (6) E.Coli + Fc NPs + Xe lamp.
[0048] (2) After the above solution was irradiated with a xenon lamp for 30 min or protected from light for 30 min, it was incubated in a bacterial incubator at 37 °C for 12 h and its OD was immediately measured using an ELISA reader. 600 .
[0049] Note: All illumination groups were exposed to a xenon lamp (20 A, 15 cm) for 30 min, and all experiments were repeated 3 times. In all antibacterial tests, the final concentrations of Fc NPs and H2O2 were 0.5 mg / mL and 100 μM, respectively. The concentration of PBS buffer (pH 7.4) was 10 mM.
[0050] (3) Dilute the six groups of E. coli suspensions after incubation 200 times, take 50 μL of the bacterial diluent and spread it on the LB medium, and culture it in a bacterial incubator at 37 °C for 12 h. After the culture is completed, take a photo of the bacterial culture medium, and compare the antibacterial effects under different conditions by observing the number of E. coli colonies.
[0051] The ferrocene nanomaterials (Fc NPs) prepared in Example 1 above were characterized in terms of morphology and performance.
[0052] Figure 2 This is a scanning electron microscope image of Fc NPs. It can be seen that Fc NPs themselves are in the shape of wool balls with an average particle size of 3 μm.
[0053] Figure 3 This is the infrared spectrum of Fc NPs. It can be seen that Fc NPs and Fc(COOH)2 have a strong affinity at 1482 cm -1 There are C=C metallocene ring stretching vibration peaks at all locations, indicating that the structure of the ferrocene ring has almost no change during the synthesis process. Fc(COOH)2 has a peak at 1687 cm -1 However, for Fc NPs, the peak red-shifted to 1575 cm -1 , indicating that Fe 2+ / Fe 3+ The OH stretching vibration peak of Fc(COOH)2 is between 3200 and 2500 cm -1 but not in Fc NPs, indicating that OH was destroyed during the synthesis of nanoparticles, further proving that the coordination reaction of the carboxyl group occurred.
[0054] Figure 4 The nitrogen adsorption-desorption isotherm of Fc NPs shows that Fc NPs have a porous structure with a BET specific surface area of 263.36 m 2 g -1 The average pore size of Fc NPs was determined to be 3.9 nm based on nitrogen adsorption and desorption, indicating a mesoporous structure. Considering that Fc NPs are designed to utilize their natural peroxidase-like catalytic activity, this porous structure and large specific surface area would promote the efficient exposure of the iron active sites to H2O2 and increase the local reactive oxygen species (ROS) concentration to enhance the catalytic activity.
[0055] Figure 5 The following are the UV-visible absorption spectra of Fc NPs and Fc(COOH)2. Fc NPs have a wide range of optical absorption from 200 to 800 nm. In contrast, Fc(COOH)2 has more obvious absorption peaks at 215 nm and 255 nm.
[0056] Figure 6 This is the XPS spectrum of Fc NPs. It can be found that Fc NPs contain Fe, O, and C elements, but no N element, indicating that Fc NPs should be formed by self-coordination of the groups in 1,1-ferrocene dicarboxylic acid, and DMF may have played the role of a surfactant to prepare the ferrocene nanoparticles of the present application. Only one raw material and one solvent are needed to synthesize nanoparticles with superior performance, which shows the advantage of Fc NPs in simple and fast synthesis.
[0057] Figure 7 The XPS high-resolution spectrum of Fe 2p in Fc NPs shows that Fe 3+ and Fe 2+ The ratio of Fe to Mg is 58%:42%, indicating that the synthesized nanoparticles can stably maintain a high Fe 2+ content, which provides the possibility for long-term cyclic catalysis, thus helping to improve the catalytic efficiency of the material.
[0058] Figure 8 The UV-visible absorption spectrum curve of Fc NPs is shown with ABTS as the colorimetric substrate at pH 4.2 and in the presence of H2O2. Fc NPs can act as a catalyst to catalyze the decomposition of H2O2 to produce ·OH, which can oxidize ABTS to ox-ABTS. Ox-ABTS has a significant absorption at 415 nm, so the catalytically produced ·OH can be detected by a UV spectrophotometer. Figure 8 As shown in the figure, in the Fc NPs+ABTS+H2O2 system, the absorbance of ox-ABTS at 415 nm was higher than that of the blank group ABTS + H2O2 after continuous reaction for 180 min. The results show that Fc NPs, as a catalyst, accelerate the process of H2O2 decomposition to produce ·OH. Compared with the raw material group Fc(COOH)2+ABTS+H2O2, the catalytic activity of Fc NPs is much higher than that of the raw material Fc(COOH)2, and the ABTS absorption peak position of Fc(COOH)2 at 415 nm has a red shift, which may be due to a side reaction, which has a certain inhibitory effect on its catalytic H2O2. This proves that after the formation of nanoparticles, Fc NPs have a more efficient and longer-lasting catalytic effect than the raw materials.
[0059] Fig. 9 The Fe content in the material after long-term catalysis of Fc NPs for different periods of time 2+ with Fe 3+ Ratio change over time. For ordinary iron-based nanomaterials, as the catalytic time increases, H2O2 will continuously consume Fe 2+ , converting it into Fe 3+ , and this process is usually irreversible and difficult to obtain from Fe 3+ Back to Fe 2+ Therefore, the catalytic effect will gradually decrease and quickly become ineffective, making it difficult to make Fe 2+ and Fe 3+ Cycle. Figure 8 It can be found that as the catalytic time increases, the Fe 2+ The proportion of Fe 2+ Only 6% Fe was reduced 2+ This indicates that the special structure of FcNPs makes Fe 2+ It can exist stably and catalyze the reaction to generate Fe 3+ It is also easier to convert into Fe 2+ , promoting the cycling of iron valence states and long-term catalysis.
[0060] Fig.10 This is a picture of the survival rate of E. coli after incubation in the dark or under xenon lamp for 12 hours. In order to explore the long-term inhibitory effect of FcNPs on the proliferation of E. coli and the antibacterial effect of xenon lamp, the bacteria were treated with xenon lamp for 30 minutes and protected from light for 30 minutes, and then incubated with the material for 12 hours, and the OD was detected by microplate reader. 600 , and then compare the bacterial survival rates of different treatment groups. Compared with the PBS control group, the survival rate of E. coli added with Fc(COOH)2 decreased slightly, indicating that it has a certain antibacterial effect, but the effect is not significant; while the survival rate of E. coli bacteria added with Fc NPs decreased significantly, proving that FcNPs have a significant antibacterial effect. In addition, under the irradiation of xenon lamp, the bacterial survival rate of Fc(COOH)2 and Fc NPs groups decreased significantly, proving that xenon lamp can promote the photocatalytic performance of materials, thereby increasing the production of •OH and enhancing the antibacterial effect.
[0061] Fig.11 This is a plate photo of 6 groups of E. coli with different treatments inoculated on LB medium and incubated for 12 hours. Fig.10 Similar results: the number of bacterial colonies in the Fc NPs group under xenon lamp irradiation was the least, while the PBS group as the control group had the most bacteria, which intuitively demonstrated the excellent antibacterial properties of Fc NPs.
[0062] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A ferrocene nanoparticle, characterized in that: The ferrocene derivative is dissolved in a solvent, reacted, centrifuged, washed and dried to obtain the product; the reaction is carried out in an autoclave at 120-200°C for 5-10 hours; The ferrocene derivative is 1,1-ferrocene dicarboxylic acid; and the solvent is N,N-dimethylformamide.
2. The ferrocene nanoparticles according to claim 1, characterized in that The nanoparticles are in a uniform spherical shape and have a particle size of 1 to 5 μm.
3. The ferrocene nanoparticles according to claim 1 or 2, characterized in that The washing is water washing.
4. The method for preparing ferrocene nanoparticles according to claim 1, characterized in that: The following steps are involved: (1) dissolving a ferrocene derivative in a solvent; (2) pouring the solution of step (1) into an autoclave and keeping it at 120-200°C for 5-10 hours; (3) Centrifuge, wash and dry.
5. Use of the ferrocene nanoparticles according to claim 1 as a catalyst for catalyzing the decomposition of H2O2 to produce •OH.
6. Use of the ferrocene nanoparticles according to claim 1 as a catalyst in photocatalytic sterilization.
Citation Information
Patent Citations
Ferrocenyl metal organic framework nanoparticle and preparation method thereof
CN113368240A
Process for preparing ferrocene and its derivative nano material
CN1900097A